Approximation Theorems for Complex Szasz-Kantorovich Operators - Mahmudov, N. I.; Kara, M. (Eudoxus Press, Llc, 2013)
In this paper, the order of simultaneous approximation and Voronovskaja-type results with quantitative estimates for complex Szasz-Kantorovich operators attached to analytic functions on compact disks are obtained.
Keywords: Szasz-Mirakjan operator; Szasz-Kantorovich operator; complex approximation